End-user centeredness in antiretroviral therapy services in Nigerian public health facilities - Chiegil, RJ; Zungu, LI; Jooste, K (South African family practice, 2014)
Objective: To describe the perception of end users with regard to end-user centeredness in antiretroviral therapy (ART) service provision in Nigerian public health facilities. Design: A qualitative design was followed. Subjects and setting: Unstructured focus group discussions were conducted with end users (n = 64) in six locations across the six different geopolitical zones of Nigeria. Outcome measures: Data were analysed using the framework approach and Weft QDA® version 1.0.1. qualitative data analysis software. Results: The results focused on end users' participation in their care, ranging from understanding their diagnosis, choosing from available treatment options and places, and caring for their colleagues and themselves. Conclusion: End-user focused ART service provision positions end users to play key roles in decision-making with regard to their care. The findings of this study will be useful for nurses and other healthcare workers when promoting end-user centeredness in ART service provision.